Added Value of Rescue Devices in Intra-Arterial Thrombectomy: When Should We Apply Them? - Ni, Cheng-Fu; Cheng, Sho-Jen; Chen, Cheng-Yu; Yeh, Tu-Hsueh; Hsieh, Kevin Li-Chun (Frontiers in Neurology, 2021)
Introduction Recent trials have demonstrated the superior efficacy of mechanical thrombectomy over other medical treatments for acute ischemic stroke. However, not every large vessel occlusion (LVO) can be recanalized using a single thrombectomy device. Rescue devices were proved to increase the reperfusion rate, but the efficacy is unclear. Objective: In this retrospective study, we evaluated the efficacy of rescue therapy in different location of LVO. Methods We analyzed the outcomes of mechanical thrombectomy from a prospective registry of consecutive 82 patients in Taipei Medical University Hospital. The reperfusion rate and the functional outcome were compared in patients who received first-line therapy only and patients who need rescue therapy. Results An 84.1% reperfusion rate was achieved in our cohort. We applied first-line stent retriever (SR) treatment in 6 patients, among which 4 (66.6%) achieved successful reperfusion. We applied a direct-aspiration first-pass technique (ADAPT) as the first-line treatment in 76 patients, among which 46 (60.5%) achieved successful reperfusion. Successful reperfusion could not be achieved in 30 cases (39.5%); therefore, we applied a second-line rescue SR for 28 patients, and reperfusion was established in 18 (64.3%) of them. Our result revealed that the LVO in anterior circulation has higher chance to response to SR rescue therapy than posterior circulation lesions (68.0% vs 33.3%, P < .001). Patients who received first-line therapy only exhibited significantly better functional outcomes than those who also treated with rescue SR therapy (41.2% vs 16.7%, P=.001). Moreover, patients with LVO in the anterior circulation were found to have a higher probability of achieving functional independence than patients with posterior circulation lesion (10.7% vs 0.0%, P < .001). The adjusted multivariate analysis revealed that successful reperfusion and treatment type (first-line or rescue therapy) were significantly related to mRS score at 90 days. Conclusion Our study reveals that rescue SR therapy improves reperfusion rate. Patients who require rescue SR therapy have a lower likelihood of functional independence. LVO in the anterior circulation responds better to rescue SR therapy than posterior circulation lesions.